(untitled) (Castilla. Estudios de Literatura, 2022)
This article analyses the onomastic play in Alfonso de Palencia’s Batalla campal de los perros contra los lobos, an important aspect for the understanding of this political chronicle of mid-15th century Castile. This is an analysis that has not been done in any previous study and without which the compositional structure of the work cannot be understood. On the other hand, we find in it the most important keys to his thinking and ideas that the author would develop in his best-known works.